Volume 2B: Turbomachinery 2019
DOI: 10.1115/gt2019-90733
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Combustor-Turbine-Interaction in a Rotating Cooled Transonic High-Pressure Turbine Test Rig: Part 1 — Experimental Results

Abstract: Within the scope of European Commission FP7 project FACTOR, dedicated to combustor-turbine-interaction research, a clean-sheet design of a rotating turbine test rig featuring a non-reacting combustor simulator was created and built among the partners. German Aerospace Center DLR provided the operational facility NG-Turb to which the rig was adapted and was responsible for global rig integration and operation, also including aerodynamic probe measurements of the flow field. The rig and experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Koupper et al [91], Bacci et al [165,166], Koupper et al [167], Krumme et al [168], and Gövert et al [169] developed an engine-representative combustor simulator dedicated to reproducing the expected turbine inlet profiles in terms of stagnation pressure, stagnation temperature, and flow field within the "Full Aerothermal Combustor-Turbine interactiOns Research" (FACTOR) project co-funded by the European Commission. The aims of the project were to develop both a trisector to be tested at the University of Florence (Florence, IT) and a full annular rig to be tested at DLR in Göttingen (DE).…”
Section: Combustor Simulators For Combustor/turbine Interaction Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Koupper et al [91], Bacci et al [165,166], Koupper et al [167], Krumme et al [168], and Gövert et al [169] developed an engine-representative combustor simulator dedicated to reproducing the expected turbine inlet profiles in terms of stagnation pressure, stagnation temperature, and flow field within the "Full Aerothermal Combustor-Turbine interactiOns Research" (FACTOR) project co-funded by the European Commission. The aims of the project were to develop both a trisector to be tested at the University of Florence (Florence, IT) and a full annular rig to be tested at DLR in Göttingen (DE).…”
Section: Combustor Simulators For Combustor/turbine Interaction Analysismentioning
confidence: 99%
“…However, in the ducted configuration, LES and HWA agreed well with the timescale maps, and continuously increasing computational capabilities will help reduce local errors by means of a higher number of through flows. Based on the activity carried out on the trisector, the rotating rig was designed and manufactured and its main characteristics are described by Krumme et al [168], where the main issues that were overcome are also reported. Gövert et al [169] also performed an integrated simulation of the annular rig, even though only a sector of 18 • was considered thanks to the periodicity of the configuration, thus using a computational domain similar to the one used by Koupper et al [170].…”
Section: Combustor Simulators For Combustor/turbine Interaction Analysismentioning
confidence: 99%
See 1 more Smart Citation